Jini to the rescue [computer network interconnection technology]. - Morgan, S. (IEEE spectrum)
A new approach to creating networks could simplify their construction end adaptation-if some kinks in the current specification can be remedied and missing features added. At the center of Jini connection technology is a lookup service, which resides on a server in a network. Its job is to act as a central market for Jini services scattered around the network, grouping similar ones together and making them accessible to client application programs. To become part of the market, a service first uses the discovery protocol to find a lookup service and then uses the join protocol to register and thus become available to client applications. Once clients and services are paired up, they no longer need the lookup service's assistance and can work together directly